Commerce in Macau (1892)
Official dispatch from the Portuguese Consulate in Canton, dated 24 May 1892, addressed to Dr. Demétrio Cinatti and copied to Mr. Ct. Atyras de Gonçalves All. and an unnamed British official. The document analyses three parliamentary proposals concerning a proposed 50% customs duty reduction on goods originating from Macau, intended to stimulate its economy. The first proposal, by Deputy Mota e Costa, advocates a 50% rebate on shared duties for industrially produced Macanese goods shipped directly to Portugal. The second, Bill No. 84, limits the benefit to goods transported on Portuguese vessels, effective from 1 July 1892, while the third, by Peer Coude de Castro, extends the reduction to all Macau-origin goods cleared at Canton and adjacent islands. The author critically evaluates each, warning that the third is overly liberal and risks benefiting foreign enterprises more than Portuguese interests. Emphasising Macau’s entrepôt function and limited industrial capacity, the consul argues that previous incentives, such as the 1889 25% tea bonus, yielded no tangible results. He highlights severe fiscal implications: potential annual revenue losses exceeding 1,600 contos de réis due to displaced domestic production and expanded colonial competition, particularly disadvantaging African territories. Noting that Macau’s trade is largely controlled by Chinese and foreign actors, he cautions against measures enriching foreign capital at the metropole’s expense. Instead, he proposes a moderate 10–15% tariff reduction combined with a 36 contos subsidy to secure regular shipping services, ensuring economic stimulus without disproportionate cost or loss of state revenue.
Keywords: 1889 Tea Bonus; Atyras de Gonçalves All.; Colonial Commerce Policy; Colonial Revenue Concerns; Consul Critical Evaluation; Demétrio Cinatti correspondence; Deputy Mota e Costa initiative; Economic Stimulation Proposal; Fiscal Revenue Loss; Historical Diplomatic Archives; Limited Industrial Capacity; Macao Trading Hub; Macau customs duty reduction; Macau entrepôt function; Portuguese Colonial Administration; Portuguese Consulate in Canton; Portuguese vessels trade benefit; Tariff Reform Impact; Transcription; industrially produced Macanese goods; late Qing China economy; parliamentary proposals Macau tariffs; unnamed British official